DREAMS: diagnosis, rights, education, available aid, mental health support, social support - Jaris, Nor Hidayah; Mohamed Ali, Iman; Mohd Kamil, Nurul Aqma; Ngimron, Anie Farhana; Zainal Abidin, Aiza Nur Izdihar; Miptah, Hayatul Nawwar; Abd Halim, Haizlene; Razali, Salmi (Faculty of Medicine, 2025)
Lack of information on the support and services related to children with learning disabilities significantly impacts the mental health of parents and caregivers. Limited knowledge and support not only make it difficult for them to understand their child’s condition but also restrict their ability to seek early intervention and fully utilise the resources necessary to support their child’s development1. The inadequacy contributes to more significant psychological distress, such as stress, anxiety, and depression.